Corporate finance in developing countries : an analysis of dividend policy among publicly listed firms in Jamaica - Robinson, C. Justin (2006)
Presents a literature review and the results of a descriptive analysis of dividend policy in Jamaica, that also provides some preliminary evidence on 'dividend disappearance' in the Jamaican context.